FAKTOR FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Siti Mutmainnah; Iwan Budiyono; Suryani Sri Lestari; Siti Hasanah; Mustika Widowati (Politeknik Negeri Semarang, 2022)
This study aims to analyze and obtain empirical evidence about the influence of professionalism, competence, independence and accountability on audit quality, both simultaneously and partially on corporate public accounting firms in Semarang. Data collection was carried out by survey using a questionnaire in the research area in the city of Semarang. The population in this study were all auditors at public accounting firms in Semarang. The model of analysis in this study uses several regression analysis model techniques and linear analysis used is the F test, t test and R2. The results of proving the hypothesis and discussion show that professionalism partially has a positive and significant effect on Audit Quality, Competence partially has a negative and insignificant effect on Audit Quality, Independence partially has a negative and insignificant effect on Audit Quality, Accountability partially has a negative and insignificant effect. on Audit Quality. Furthermore, professionalism , Competence, independence,and accountability simultaneously have a significant effect on Audit Quality.